Importance of Education in Mother Language for Iranian Bilingual Students - Seifi, Pouran (Advances in Social Sciences Research Journal, 2014)
Abstract Language is the very essence of communication in class but submersion instruction makes students frustrated and increases underachievement in non-Persian Iranian students. Teachers report diversity of problems in students learning process and parents are struggling with their children’s educational problems in elementary grades mostly. It seems that application of strong type of bilingual education like immersion is recommended in most provinces of Iran in order to provide students with a warm and pleasant learning situation by respecting their rights as learning in their mother language and helping them develop to the highest level of their potentials in the society by leaning national language. This lead students, their families and communities to feel they belong to this country. Consequently, the unity of the country will be strengthened. Key words: mother language, underachievement, bilingual education